Pelatihan Tertib Administrasi Kelompok Pembudidaya Ikan “Mino Djoyo” Pasekan, Yogyakarta - Wulandari, Ika; Utami, Endang Sri; Budiantara, Martinus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
This Community Service activity is carried out with the aim of providing understanding, knowledge and skills in an effort to support an orderly administration at KPI “Mino Djoyo”. The background of this program implementation is because KPI “Mino Djoyo” has not properly recorded the financial administration and administration of group activities. The method of implementation is carried out by providing counseling and training which is carried out in two stages. The first counseling was held on October 31, 2020 and was attended by 16 members. The second training was held on November 1, 2020 and was attended by 3 KPI “Mino Djoyo” administrators, namely treasurers, deputy treasurers and secretary representatives. As a result of PkM's activities, KPI “Mino Djoyo” already has administrative books that are well-organized and neat, such as minutes, lists of members & administrators, correspondence books, guest books, cash books, inventory books and simple financial records. Increased understanding and knowledge of the management regarding the importance of orderly administration and how to implement it.